2001
DOI: 10.2337/diacare.24.7.1187
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hemochromatosis C282Y and H63D Mutations in HFE Gene in Development of Type 2 Diabetes and Diabetic Nephropathy

Abstract: OBJECTIVE -In patients with clinical hemochromatosis, the frequency of diabetes ranges from 20 to 50%, and the heterozygosity for the C282Y mutation in the HFE gene might be associated with an increased risk for diabetes. There are also some reports that suggest that iron overload might cause diabetic nephropathy.RESEARCH DESIGN AND METHODS -We performed an association study to assess the role of the C282Y and H63D mutations in the HFE gene as a risk factor for type 2 diabetes and diabetic nephropathy. Altoget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
57
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 28 publications
(29 reference statements)
5
57
0
3
Order By: Relevance
“…There have been reports of significant increases in the frequency of HFE mutations in diabetes clinic populations [26,27], although other studies have failed to see such increases [28][29][30][31][32]. If the frequency of haemochromatosis subjects in white populations is 0.5% [1,2] and 20% of those adults have diabetes, then the frequency of adult diabetic individuals with haemochromatosis in the population will be approximately 0.1%.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports of significant increases in the frequency of HFE mutations in diabetes clinic populations [26,27], although other studies have failed to see such increases [28][29][30][31][32]. If the frequency of haemochromatosis subjects in white populations is 0.5% [1,2] and 20% of those adults have diabetes, then the frequency of adult diabetic individuals with haemochromatosis in the population will be approximately 0.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In 1994, it was reported (Nankivell et al 1994) that iron overload might cause diabetic nephropathy through accumulation in tubular lysosomes. Moreover, Moczulski et al (2001) have recently reported that hemochromatosis-causing mutation H63D, but not C282Y, predisposes to diabetic nephropathy. It has been demonstrated that the C282 mutation alters the HFE protein structure and beta 2 -microglobulin association or cell-surface expression, whereas the H63D mutation, in contrast, does not appear to prevent beta 2 -microglobulin association or cell-surface expression, indicating that the C282 mutation results in a greater loss of protein function than does H63D , Lebron et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the frequency of HFE mutations is increased in type 2 diabetes, probably in relationship with liver iron overload (11)(12)(13)(14)(15)(16). Nevertheless, the Rotterdam study has not found an increase of the frequency of HFE mutation in patients with glucose intolerance or type 2 diabetes by comparison with general population or in case control studies (9,17,18).…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, only 43% of the control group had an abnormal HFE genotype, with no case of HH and the same prevalence of H63D heterozygosity than in the D group. When we compared our data to other genotype analyses according to diabetes status (11)(12)(13)(14)(15)(16)(17)(18)(19), we found a much higher frequency of HFE gene mutations (21% C282Y homozygote) in the Lille series. This can be explained by the fact that we did not perform genotyping systematically, but only when iron parameters were disturbed.…”
Section: Discussionmentioning
confidence: 90%